A water-soluble core material for manufacturing hollow composite sections - Xiao, Z.; Harper, L.T.; Kennedy, Andrew R.; Warrior, N.A. (Elsevier, 2017)
This paper presents the development of a low-cost water-soluble core material, which is suitable for producing hollow composite structures via high pressure moulding processes, such as compression moulding and resin transfer moulding. The bulk material of the core is sodium chloride (NaCl), which is held together by a watersoluble trehalose binder. The composition of the core has been optimised to provide acceptable dissolution rates and mechanical properties for high volume structural composite applications. The compressive strength of the NaCl core was 57 MPa at ambient temperature, which reduced to 20 MPa when tested at 120 °C. The compressive strength at elevated temperature was approximately 4 times higher than for a water-soluble commercial benchmark and 33 times higher than a conventional structural closed-cell foam. The specific dissolution rate of the NaCl core was between 0.14 and 1.23 kg/(min·m2), depending on processing parameters and the coefficient of thermal expansion was approximately 43 × 10−6/K. A practical example has been presented to demonstrate how the removable core can be used to produce a representative hollow section of an integrally stiffened panel.